(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Promoting physical activity through urban infrastructures is a major public health priority. In Anglet (France), the “Health Paths” (locally known as “Chemins de la Forme”) are designed to encourage health-enhancing physical activity among residents. This study assesses their impact, focusing on differences between users and non-users across activity intensities. Methods: A cross-sectional study was conducted with 257 participants (age mean: 47.4 years, 51% women) living in Anglet and surrounding areas. Participants completed a validated 15-minute questionnaire (IPAQ-SV) measuring weekly physical activity across light (LPA), moderate (MPA), and vigorous (VPA) intensities. Group comparisons (users vs non-users of the “Health Paths”) were performed using non-parametric tests (Wilcoxon–Mann–Whitney, Chi-Square) and regression analyses explored factors associated with activity levels, controlling for socio-demographic variables. Results: Among participants, 234 (91%) reported a regular weekly use of “Health Paths”. The primary motivation reported was to improve health. Users demonstrated higher LPA (782 vs 604 METs-min/week-1, p = 0.172) and MVPA (1,538 vs 1,264 METs-min/week-1, p = 0.102) compared to non-users, although these differences were not statistically significant. However, regression analyses highlighted that frequency of use was positively associated with overall physical activity (β = 0.138, p = 0.002) and LPA (β = 0.181, p = 0.007) but not with MVPA (β = 0.123, p = 0.106). Conclusion and Implications: While the “Health Paths” effectively increase LPA, they do not significantly increase MVPA levels, which are critical for maximising health benefits according to WHO guidelines. These findings underscore the need for complementary strategies to promote MVPA, aligning with existing literature advocating for multi-level interventions. Support/Funding Source: None. Keywords: Urban environment, energy expenditure, public health